The Effect of the Problem Based Learning Model on Critical Thinking Skills in Indonesian Language Learning for Grade IV Students - Viyanti, Pratiwi; Moh Faiz Shofi; Evi Wiyanti (AT-THULLAB : Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2025)
This research aims to investigate the application of the Problem-Based Learning (PBL) model and its impact on the critical thinking abilities of fourth-grade students. A mixed-method design was employed, utilizing a quasi-experimental one-group pretest-posttest format. Data were gathered through interviews, observations, questionnaires, documentation, and critical thinking assessments. Data analysis followed a Sequential Exploratory strategy, beginning with the collection of qualitative data and subsequently proceeding to quantitative analysis. The implementation of PBL was conducted in six structured sessions, which included icebreakers, group discussions, text analysis, sentence construction, story writing, and presentations. Results showed that PBL enhanced students' participation, motivation, self-confidence, and critical thinking skills, particularly in identifying problems, analyzing information, drawing logical conclusions, evaluating solutions, and communicating ideas. Quantitatively, the average pre-test score of 61.87 increased to 71.13 in the post-test, with a significant difference (t = -6.038; p < 0.05). Therefore, PBL positively influenced learning outcomes and fostered critical, creative, communicative, and collaborative competencies in language learning.